(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction- A prospective study of closed Mitral Valvotomy in 104 patients Method and Result- From December 2012 to December 2019, 104 patients underwent CMV. 94 Patients become symptom free after surgery and only 7 patients required Mitral valve replacement surgery on followup Conclusion- Closed Mitral Valvotomy represents a satisfactory technique in terms of lower cost, high efficacy, simplicity and reproducibility